2018
DOI: 10.1097/moo.0000000000000429
|View full text |Cite
|
Sign up to set email alerts
|

How does sinus surgery affect topical irrigation distribution?

Abstract: Purpose of review The current article reviews the literature on the distribution of nasal irrigation in the treatment of chronic sinusitis, especially in how sinus surgery and irrigation techniques affect its delivery to the nasal cavity and paranasal sinuses. Recent findings Nasal irrigation has become a useful tool in the treatment of chronic sinusitis. Used after endoscopic surgery of the paranasal sinuses, irrigation has shown to be effective in imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Hence, we can speculate that removal of the superior nasal and interfrontal septum during the Draf III procedure (with consequent flow of solution through the septal window and out the contralateral nostril) might be less relevant if the irrigant is delivered by positive pressure. This hypothesis is in accordance with the findings of de Paiva Leite and Douglas 11 who reported that Draf III procedures may reduce irrigation of the other sinuses.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Hence, we can speculate that removal of the superior nasal and interfrontal septum during the Draf III procedure (with consequent flow of solution through the septal window and out the contralateral nostril) might be less relevant if the irrigant is delivered by positive pressure. This hypothesis is in accordance with the findings of de Paiva Leite and Douglas 11 who reported that Draf III procedures may reduce irrigation of the other sinuses.…”
Section: Discussionsupporting
confidence: 93%
“…6 studied the sinus penetration of irrigant according to 3 steps of surgical dissection in 10 cadaver heads and found that a wider sinus ostium resulted in better penetration of irrigant. In addition, in a recent review, de Paiva Leite and Douglas 11 concluded that functional endoscopic sinus surgery improves the reach and delivery of irrigation solutions to the paranasal sinuses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,7 However, high-volume nasal irrigation (240 mL at least once a day) has been recommended by most experts. 7,8 The theoretical benefits of high-volume irrigation are (1) more effective debris, clots, and crusts removal and…”
Section: Introductionmentioning
confidence: 99%